Novel gain of function approaches for vaccine candidate identification in Burkholderia pseudomallei - Dowling, Andrea J. (Frontiers in Cellular and Infection Microbiology, 2013)
The Gram-negative bacterium Burkholderia pseudomallei is a serious environmental pathogen and the causative agent of the often fatal melioidosis. Disease occurs following exposure to contaminated water or soil, usually through cuts in the skin or via inhalation. However the underlying mechanisms of pathogenicity remain poorly understood. B. pseudomallei is endemic to South East Asia and Northern Australia where infections are associated with antibiotic resistance and high mortality rates. Categorization of the pathogen as a potential biowarfare agent has also made research into vaccine development a high priority. Recent genome-scale screening has produced a large number of putative gene candidates from B. pseudomallei with the potential for development into vaccines. This mini-review will discuss the advantages and limitations of this novel approach, how these new techniques can complement existing strategies, and outline aims for future research.